2016
DOI: 10.1292/jvms.15-0708
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and contamination levels of <i>listeria monocytogenes</i> in ready-to-eat foods in Tokyo, Japan

Abstract: We surveyed prevalence and contamination levels of Listeria monocytogenes in ready-to-eat foods between 2000 and 2012 in Tokyo. L. monocytogenes was isolated from 52 (1.7%) out of 2,980 samples. Comparing the prevalence in the study period, 2.2% were positive in the former period (2000–2005) and 1.2% in the latter (2006–2012). Using the most probable number (MPN) technique, 32 samples were contaminated with fewer than 0.3 L. monocytogenes/g, 10 samples with 0.3–1.0/g and 4 samples with more than 1.0/g (the max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 8 publications
4
7
1
Order By: Relevance
“…In contrast, the most common serotypes isolated from RTE food (including natural cheese, meat products, seafood and pickled vegetables) in Japan were 1/2a (47.6%), 1/2b (20.6%) and 4b (14.3%). 34 Similar findings were reported in other countries of the northern hemisphere. In Poland, Korsak et al, 35 analyzed 471 L. monocytogenes strains isolated from different foods and found the following serotype distribution: 1/2a, 54.4%; 1/2c, 25.5%; 1/2b, 12.5% and 4b 7.6%.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, the most common serotypes isolated from RTE food (including natural cheese, meat products, seafood and pickled vegetables) in Japan were 1/2a (47.6%), 1/2b (20.6%) and 4b (14.3%). 34 Similar findings were reported in other countries of the northern hemisphere. In Poland, Korsak et al, 35 analyzed 471 L. monocytogenes strains isolated from different foods and found the following serotype distribution: 1/2a, 54.4%; 1/2c, 25.5%; 1/2b, 12.5% and 4b 7.6%.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, we assessed 570 food samples in China from 2014 to 2016, 39 RTE foods and 5 pasteurized milk samples (7.7%) tested positive for L. monocytogenes, concurrent with contamination of L. monocytogenes in RTE foods reported in Beijing (Wang W. et al, 2015) but significantly greater than that of RTE foods in Estonia (Koskar et al, 2019) and Tokyo, Japan (Shimojima et al, 2016). However, Wang et al (2018) reported that 16.2% of samples were contaminated with L. monocytogenes in retail outlets selling RTE foods and restaurants serving mutton in Zigong, Sichuan Province.…”
Section: Discussionmentioning
confidence: 99%
“…ice-cream contaminated with L. monocytogenes was recalled in the US and in other countries, including Qatar or collagen protein bar and Bite products recalled from 42 countries. The concerns regarding listeriosis are not only related to the high frequency of detection of L. monocytogenes due to the bacterial ecology, but also to the category of contaminated products (usually 'ready to eat products'), which are consumed without other previous treatment (Ajayeoba et al 2016;Shimojima et al 2016).…”
Section: Introductionmentioning
confidence: 99%